Bearing capacity of footing on soft clay strengthened by lightweight expanded clay aggregate raft - Azhani, Zukri (Penerbit UMP, 2023)
This research represents an investigation into the effectiveness of replacement methods to increase the bearing capacity of soft clays under footing load, where Light Expanded Clay aggregates (LECA) were used as a substitute for common aggregate fillers. The soil replacement technique is the easiest and cheapest way to improve soft soil compared to installing a raft footing or using a deep foundation such as piles. LECA is known to be light, strong and environmentally sustainable and is widely used in Geotechnical applications where weight is an issue. The bearing capacity of the footing on soft soil reinforced by LECA was analysed through finite element analysis using commercial software PLAXIS 3D (2020). The soft ground is represented by Hardening Soil (HS) constitutive model, while LECA has been modelled as Mohr-Coulomb (MC). Parametric studies were conducted to assess the effect of LECA raft thickness to bearing capacity improvement for various friction angles of LECA. The research found that the bearing capacity is directly proportional to the internal friction angle of LECA and the LECA raft thickness. Nevertheless, the bearing capacity appears to be almost linear when 2.5 m and 3.5 m thick LECA rafts are used, indicating that the depth of replacement ratio more than 25% give insignificant effect towards improvement ratio.